INTRAORAL SCANNING AND DIGITAL TECHNOLOGY - Maria-Antonela Beldiman; Monica Silvia Tatarciuc; Anca Mihaela Vițalariu; Nicoleta Ioanid; Georgiana Macovei; Cristina Vasilache (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study Intraoral scanning records the data of structures and tissues in the oral cavity and is followed by the transmission of information in the digital workflow, which is the first step in most clinical situations. Material and methods The algorithm for performing prosthetic works and restorative structures requires the use of CAD-CAM technologies, and scanning can be performed either directly in the patient's oral cavity or by scanning models in the laboratory. The advantages of using an intraoral scanner are reflected on the multiple clinical applications of the method - for diagnostic purpose, in fixed prosthodontics, to develop a removable partial denture metal framework, in complete denture cases, implant cases, in orthodontics, etc. Results Compared to the traditional prosthesis manufacturing algorithm, the advantages of using intraoral scanners and CAD / CAM technology include simplifying the work process; qualitative standardization of the laboratory process; efficiency in the stages of performing dental prosthesis: registration, transmission and storage of patient data/information, efficient and informed communication between dentist and dental technician. Conclusions Because there are multiple advantages that can be obtained by approaching a digital workflow, digital technology is gaining more and more ground in all fields of dentistry.